Reduction of Hopelessness Through Spiritual Emotional Freedom Techniques Therapy in Chronic Kidney Disease Patients Undergoing Hemodialysis - Ode Irman; Anggia Riske Wijayanti (Fakultas Ilmu Keperawatan Universitas Indonesia, 2022)
Hopelessness has been identified as a major psychological problem that exacerbates the clinical outcomes of chronic kidney disease (CKD) patients undergoing hemodialysis (HD). Hopelessness is mostly reduced by cognitive therapy, but the results are delayed, so a spiritual element is needed. Spiritual emotional freedom technique (SEFT) therapy can reduce hopelessness because it not only focuses on cognition, but also involves spiritual, psychological, and physical elements. This study aimed to determine the effects of SEFT therapy on the hopelessness of CKD patients undergoing HD. This research was quasi-experimental with pre- and post-test control group designs. The sample size was 64 respondents, who were divided into two groups, each consisting of 32 respondents who were selected by purposive sampling. SEFT therapy was conducted four times. Hopelessness was measured using the Beck Hopelessness Scale (BHS). The data were analyzed by paired t-test and independent samples t-test. Before receiving SEFT, the two groups did not indicate differences in hopelessness (p = 0.141). However, after receiving SEFT, the respondents’ hopelessness in the experimental group was reduced significantly (p = 0.000). Hopelessness in the experimental and control groups also differed significantly after the intervention (p = 0.000). This study revealed that SEFT reduced the hopelessness of CKD patients undergoing HD. SEFT therapy can be implemented in clinical practice areas of nursing to support patient care. Keywords: chronic kidney disease, hemodialysis, hopelessness, spiritual emotional freedom technique Abstrak Mengurangi Keputusasaan Melalui Terapi Spiritual Emotional Freedom Techniques Pada Pasien Penyakit Ginjal Kronik yang Menjalani Hemodialisis. Keputusasaan telah diidentifikasi sebagai salah satu masalah psikologis utama yang memperburuk hasil klinis pasien penyakit ginjal kronik (PGK) yang menjalani hemodialisis (HD). Keputusasaan sebagian besar dikurangi dengan melibatkan unsur kognitif, akan tetapi hasilnya mengalami keterlambatan sehingga dibutuhkan unsur spiritual. Terapi spiritual emotional freedom technique (SEFT) dapat mengurangi keputusasaan karena tidak hanya berfokus pada kognitif tetapi juga melibatkan unsur spiritual, psikis, dan fisik. Penelitian ini bertujuan untuk mengetahui pengaruh terapi SEFT terhadap keputusasaan pasien PGK yang menjalani HD. Penelitian ini merupakan quasi-experiment dengan rancangan pretest dan posttest control group. Besar sampel sebanyak 64 responden yang dibagi menjadi dua kelompok, dan masing-masing kelompok terdiri dari 32 responden dipilih secara purposive sampling.Terapi SEFT dilakukan sebanyak empat kali. Keputusasaan diukur menggunakan Beck Hopelessness Scale (BHS). Data dianalisis dengan uji paired t-test dan uji independent samples t-test. Sebelum menerima SEFT kedua kelompok tidak menunjukkan perbedaan keputusasaan (p = 0,141). Namun, setelah menerima SEFT, keputusasaan responden di kelompok eksperimen berkurang secara signifikan (p = 0,000). Keputusasaan pada kelompok eksperimen dan kontrol juga berbeda secara signifikan setelah intervensi dilakukan (p = 0,000). Studi ini mengungkapkan bahwa SEFT mengurangi keputusasaan pasien PGK yang menjalani HD. Terapi SEFT dapat diimplementasikan dibidang praktik klinis keperawatan untuk mendukung perawatan pasien. Kata Kunci: hemodialisis, keputusasaan, penyakit ginjal kronik, spiritual emotional freedom technique